2017
DOI: 10.1590/1984-0462/;2017;35;3;00009
|View full text |Cite
|
Sign up to set email alerts
|

Qualidade De Sono E Sua Associação Com Sintomas Psicológicos Em Atletas Adolescentes

Abstract: Objective: To verify the prevalence of poor sleep quality and its association with personal characteristics and symptoms of depression, anxiety and stress in amateur adolescent athletes. Methods: 309 adolescent athletes aged between 10 and 19 years were enrolled. Data collection included: a structured questionnaire, with personal information; the Pittsburgh Sleep Quality Index (PSQI); and the Depression, Anxiety and Stress Scale (DASS-21). Results are described in mean and standard deviation (numeric variables… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
10
0
5

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(20 citation statements)
references
References 30 publications
(34 reference statements)
3
10
0
5
Order By: Relevance
“…The rates of anxiety and depression among our participants are very high, as other reports from studies conducted among adolescents elsewhere. 23 , 35 Our study also revealed that the participants’ sleep quality was significantly associated with these health conditions, as in other studies. 10 , 11 The composite relationship between sleep and psychological disorder, such as anxiety and depression in adolescents, has attracted much attention over time.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…The rates of anxiety and depression among our participants are very high, as other reports from studies conducted among adolescents elsewhere. 23 , 35 Our study also revealed that the participants’ sleep quality was significantly associated with these health conditions, as in other studies. 10 , 11 The composite relationship between sleep and psychological disorder, such as anxiety and depression in adolescents, has attracted much attention over time.…”
Section: Discussionsupporting
confidence: 88%
“… 21 Similarly, the number of internet users and abusers among adolescents in Nigeria has continued to rise, 22 and the figure of adolescents suffering from psychological problems has equally increased. 23 In a locale where data is grossly insufficient, it is apt to fill in gaps in information by conducting studies of this nature, which may be useful for other researchers, clinicians, and policymakers. With the increasing concern about students’ mental health in recent years, it is, therefore, necessary to update the prevalence of PSQ among secondary school students, identify sociodemographic factors associated with it in this group, and to examine the independent associations of psychological distress, stimulant use, and internet use with PSQ.…”
Section: Introductionmentioning
confidence: 99%
“…It is added that anxiety is a complete emotion acting on the physical and mental aspect of the individual, which, depending on the intensity and frequency, may be pathological or not. [1][2][3][4][5][6][7] It should be emphasized that the first choice treatment for anxiety and depression are psychoactive drugs and that, although this drug class causes severe side effects, its use is increasingly widespread, adopted in an early and indiscriminate way. Benzodiazepines -medication of the anxiolytic class -are the most prescribed drugs in the world, perhaps due to the growth of diagnoses of mental disorders in the population.…”
mentioning
confidence: 99%
“…Chronological age can negatively interfere with the assessment of QOS. With advanced age, the hours of sleep tend to decrease, thus, poor self-perceived QOS can be seen 25,26 . The age of the participants in the control group was slightly higher than the participants with T1DM (Table 1), however, when correcting the analysis according to age, only the girls in the control group remained with QOS in lower class parameters.…”
Section: Discussionmentioning
confidence: 99%